The Relationship Between Self-Management and Quality of Life in Type 2 Diabetes Mellitus Patients of Productive Age - Belinda Natasia; Yosi Suryarinilsih; Yessi Fadriyanti; Nova Yanti; Indri Ramadini (Fakultas Keperawatan Universitas Andalas, 2025)
The increasing incidence of diabetes mellitus among individuals of productive age requires special attention, as poor self-management can reduce overall quality of life and productivity, especially in productive age groups with work, social, and family demands, which can affect adherence to self-management. Although self-management theoretically influences quality of life, the relationship between the two is still debated by researcher. This study aims to determine the relationship between self-management and quality of life in productive-age type 2 diabetes. The study used a cross-sectional design conducted from December 2024 to June 2025. The study population was 132 productive-age type 2 diabetes mellitus patients, with a sample size of 63 respondents selected through a purposive sampling technique. The instruments used were the Revised Version of Diabetes Quality of Life Instrument (DQoL) to assess quality of life and the Summary of Diabetes Self-Care Activities (SDSCA) to assess self-management. Data were analyzed univariately and bivariately. The results showed that more than half of respondents (63.5%) had a high quality of life and more than half (52.4%) had good self-management. Statistical tests using chi-square showed a p value = 0.017 (p < 0.05), which means there is a significant relationship between self-management and quality of life. These results indicate that the better the self-management, the higher the quality of life of productive-age type 2 diabetes patients. Therefore, it is recommended that health workers can intervene in diabetes management by paying attention to psychosocial aspects, including coping strategies, education for the social environment, and counseling to reduce the emotional burden on patients.